Role of flurochrome stain in the diagnosis of leprosy - Ahamad, M Shahab Uddin; Ahmed, ASM Mostaque; Rahman, AJEN (Journal of Chittagong Medical College Teachers' Association, 2009)
doi: 10.3329/jcmcta.v19i1.3845 Journal of Chittagong Medical College Teachers' Association 2008: 19(1):15-16